PROSEDUR AUDIT UNTUK PERUSAHAAN BERBISNIS TANAMAN SAWIT DALAM UPAYA MENCEGAH TERJADINYA SALAH SAJI LAPORAN KEUANGAN - Yannes Manurung (Jurnal Liabilitas, 2023)
The purpose of this study is to determine audit risks that may arise from audit procedures when carrying out audit procedures, resulting from missing a procedure that must be carried out or a lack of understanding of the client's business, so that misstatements made by the client become uncorrected which causes the presentation of financial statements to not reflect the current state of affairs. which are actually. It is undeniable, the Covid-19 outbreak has had a huge impact on human life patterns, especially interactions between humans both with outsiders of the family and with internal parties in the family, carrying out business activities and living a working life in earning a living. Likewise in the work scope of audit services, the impact of changing patterns of life also affects the planned work pattern at the Public Accounting Firm. As time went by, when the government succeeded in overcoming the development of the covid outbreak, the work pattern at the Public Accountant Firm also changed where currently the audit has even implemented inspections at the client's office. In order to avoid misstatements, the auditor must carry out field checks